A Retrospective Exploration of Targeted Maintenance Therapy in Advanced Colorectal Cancer: Based on the Background of Chinese Patient Assistance Program - Hu, Hanguang; Liu, Xue; Cai, Wen; Wu, Dehao; Xu, Junxi; Yuan, Ying (Frontiers in Oncology, 2020)
Background: Maintenance therapy with bevacizumab (Bev) in patients with colorectal cancer (CRC) provides progression-free survival (PFS) benefits. However, the role of maintenance therapy with an anti-EGFR monoclonal antibody has not been established. Methods: Eligible CRC patients were assigned to maintenance therapy with cetuximab (Cet; Cet group) or Bev (Bev group). PFS, the duration of maintenance therapy, and safety were analyzed. Cox multivariate regression analyses were performed to determine independent prognostic factors. Results: A total of 143 eligible patients were assigned to the Cet (n = 79) or Bev (n = 64) groups. In the Cet group, all patients had KRAS wild-type. The baseline characteristics were well-balanced between the two groups, except for a higher percentage of patients with a left-sided primary tumor in the Cet group than in the Bev group (86.1 vs. 62.5%, P < 0.0001). The median PFS was not significantly different between the Cet group and the Bev group: 5.9 months (95% CI 2.30–9.50) vs. 7.0 months (95% CI 3.69–10.31) (HR 1.17, 95% CI 0.77–1.79, P = 0.45). The median duration of maintenance therapy in the Cet group was shorter than that in the Bev group: 4.0 months (95% CI 1.94–5.99) vs. 4.8 months (95% CI 2.68–6.98) (HR 0.90, 95% CI 0.61–1.33; P = 0.59). The subgroup analyses showed that the median PFS for the first maintenance therapy and the second maintenance therapy were 3.2 months (95% CI 1.69–4.78) and 5.2 months (95% CI 1.58–8.83), respectively (HR 0.89, 95% CI 0.44–1.81; P = 0.75). Conclusions: This study suggests that maintenance therapy with Cet or Bev can be considered an appropriate option following induction chemotherapy for selected patients with advanced CRC. Multiple maintenance therapy seems to confer survival benefits in advanced CRC. Maintenance therapy with Cet after first-line induction chemotherapy seems to be associated with greater survival benefits.